Exploiting solitons in all-optical networks. - Atieh, Ahmad K. (University of Ottawa (Canada), 1997)
Two key components, the pulse generator and optical signal demultiplexer, needed for the implementation of all-optical soliton-based local area and wide area networks are investigated. The technology of generating a bright soliton pulse train from a sinusoidal pulse train produced as the beat signal of two distributed feedback laser diodes passed through a so-called comblike fiber structure is developed. A design methodology for this structure is discussed, and using this approach a soliton pulse source is constructed generating 1553 nm pulses at a repetition rate of 50 GHz, with pulses of full width at half maximum of 2.0 ps. The fiber structure used to generate the bright soliton pulse train employs the lowest average power for the beat signal ever reported in the literature, and the shortest length of fiber. The same structure (with a different design) is also used to produce a 47.6 GHz dark soliton pulse train with a full width at half maximum of 3.8 ps. This is the first reported use of this structure to generate dark solitons. It is shown that the comblike dispersion profile fiber structures may also be exploited for soliton pulse compression producing widths as short as 200 fs. Two approaches to implementation of optical signal demultiplexing are discussed. These are the nonlinear optical loop mirror (NOLM) and the separation of multilevel time division multiplexed signal pulses in the frequency domain by exploiting the relationship between the pulse's energy (i.e. pulse amplitude and width) and the Raman self-frequency shift. A modification of the NOLM scheme is investigated where feedback that adjusts the power of the control signal (by controlling the gain of an erbium-doped fiber amplifier introduced into the control signal input path) is employed to make the structure insensitive to the state of polarization of the signal and control pulses. In order to better understand the physical phenomena exploited in optical fiber soliton transmission and the above schemes, two experiments are conducted to measure the fiber nonlinear ratio $(n\sb2/A\sb{eff})$ and the Raman time constant $(T\sb{R})$ in single-mode fibers at 1550 nm. The fiber nonlinear ratio was measured for standard telecommunication fiber, dispersion shifted fiber, and dispersion compensating fiber. A value of 3.0 fs for the Raman time constant was measured and is recommended for soliton pulse propagation modeling in single-mode optical fibers.
Keywords: Engineering, Electronics and Electrical.